SOIL BIOGENICITY OF WILT-INFECTED COTTON FIELDS DURING PLOWING OF VARIOUS PLANT RESIDUES - Abboskhon, Marupov; Gulshod, Turamuratova (PT. Antis International Publisher, 2024)
The model experiment results reveal that easily mobilized organic matter introduced into the soil is absorbed much faster by bacteria than by fungi during the initial decomposition phase. This study examines the influence of composting duration of various plant residues on soil biogenicity, microbiological activity, and V. dahliae development. Findings indicate that the composition of organic matter affects the quantity and type of microorganisms in soil as well as its biological activity. Increased bacterial and fungal populations correlate with available organic resources. Addition of plant residues enhances soil microbiological activity while reducing its fungistatic potential. In conclusion, heightened activity of antagonistic bacteria and fungi through plant residue enrichment augments soil fungistatic activity, inhibiting the growth of Fusarium sp. and V. dahliae pathogens.